DXXK exerts anti-inflammatory effects by inhibiting the lipopolysaccharide-induced NF-κB/COX-2 signalling pathway and the expression of inflammatory mediators. (3rd February 2016) - Yu, Ya; Li, Xiang; Qu, Liping; Chen, Yang; Dai, Yanping; Wang, Mei; Zou, Wenjun
Abstract: Ethnopharmacological relevance: Diao Xin Xue Kang (DXXK) is the active pharmaceutical ingredient of the traditional Chinese medicinal product DXXK capsules, which have been approved for the treatment of cardiovascular disease and have been widely used clinically in China for many years with distinct curative effects. In March 2012, DXXK capsules were approved in the Netherlands, making them the first traditional herbal medicinal product (THMP) made outside of Europe. Aim: To assess the anti-inflammatory effects of DXXK and the underlying mechanisms at the cellular and molecular levels. Materials and methods: In this study, lipopolysaccharide (LPS) was used to induce inflammation in RAW 264.7 cells. The sulphorhodamine B (SRB) assay was used to study the effect of DXXK on the proliferation of RAW 264.7 cells. Gene expression levels of cyclooxygenase 1 (COX-1), COX-2, tumour necrosis factor-alpha (TNF-α), IL-1β and IL-6 were assessed by reverse transcription polymerase chain reaction (RT-PCR), while COX-2 protein levels were evaluated using western blotting. The levels of PGE2 in the culture media were detected by enzyme-linked immunosorbent assay (ELISA), while TNF-α, IL-1β and IL-6 levels were detected using a Milliplex Map Mouse Cytokine Panel system. The activation and nuclear translocation of nuclear transcription factor κB (NF-κB) were studied using western blotting. In vivo studies in mice were carried out using the carrageenan-air pouch models of inflammation. In exudates, leucocytes were counted, total protein was determined using the Bradford assay, nitric oxide(NO) levels were assessed using the Griess reagent, and PGE2 and TNF-α levels were quantified by ELISA. Results: The SRB assay showed that at the doses used in this study (10, 20 and 40 μg/mL), DXXK did not affect the proliferation of RAW 264.7 cells. DXXK (10, 20 and 40 μg/mL) inhibited LPS-induced PGE2 production by down-regulating the expression of COX-2, without influencing COX-1 expression. We also demonstrated that DXXK reduced the expression of pro-inflammatory cytokines, including TNF-α, IL-1β and IL-6, at both the gene and protein levels. Furthermore, DXXK inhibited LPS-induced NF-κB activation and nuclear translocation by suppressing the phosphorylation of IκB. Consistent with the in vitro results, the in vivo studies demonstrated that DXXK reduced leucocyte counts as well as total protein, NO, PGE2 and TNF-α levels in the exudates of mice with carrageenan-air pouch inflammation. Conclusions: The current study revealed that DXXK has a significant anti-inflammatory effect that may be attributed to its inhibitory effect on the NF-κB/COX-2 pathway and associated inflammatory mediators, including PGE2, NO, TNF-α, IL-1β and IL-6. The current study provides additional evidence of the effects of DXXK in inflammation. Based on the combination of our results and previously reported data, we propose that DXXK has multiple pharmacological effects that could be harnessed to treat systemic diseases. Graphical abstract: